ICU auditors‟ understanding of achieving good university governance - Arisona Ahmad; Ali Djamhuri; Ari Kamayanti (STIE Perbanas Surabaya, 2016)
This study aims to determine the Internal Control Unit (ICU) auditors’ under-standing in achieving Good University Governance (GUG) at Jember University (UNEJ). This study uses interpretive phenomenology. Method of data collection is conducted by interviewing the ICU auditors of UNEJ. The research findings indi-cate that the ICU auditors’ understanding in carrying out their function is com-pliant with the ICU charter. Through in-depth interview with informants, it is found noesis, in which the informants’ understanding is not only through the know-ledge and implementation of the existing rules, but also through cultural practices of